At night, lightening - Medina, Cuauhtémoc; Chávez Mac Gregor, Helena (Re-visiones, 2024)
We were invited by Gitanjali Dang and Christopher Schenker to participate in the Draft Project, an initiative that explores contemporary art that produces, contributes or provokes public debate. The project involved nine teams around the world that worked for twelve months in their local contexts: Beijing, Cairo, Cape Town, Hamburg, Honk Kong, Mexico City, Mumbai, St. Petersburg and Zurich. In our case, Mexico City was conformed by Helena Chávez Mac Gregor, Cuauhtémoc Medina and the artistic collective Teatro Ojo. For us, one of the questions raised by the Draft project was how to intervene within a public sphere swamped by images of violence that unlike creating a space to produce a collective thought subdues into the effects of its own violence. The local configuration of the public sphere happens as if we are isolated, staring at the catastrophe without any words to say. The images that circulate, normalized, are no longer able to open up our eyes. Its saturation no longer lights up anything. Teatro Ojo’s intervention attempts to produce a different order, sense or formation, by circulating publicly a bunch of different images. Montages trying to turn back to the public sphere –either TV or social network- and appear with the shape of lightning bolts, to establish in its sequence possible new relations. This text is the recounting of the process that lead us to At night, lightening.